Wanted by the devil eaudiobook - Blake, Joanna (Devil's Riders, 2018)
I've waited years for her to grow up. Now it's time. I won't be gentle and I won't be kind. I'm taking what is mine. Kaylie Wherever I went, I heard it: the sound of a purring motorcycle behind me. They never bothered me or said a word. But I knew they were there because of him. Devlin McRae, the head of the local MC. Being followed all the time like this was disconcerting. And lately, the bikes had been getting closer, less secretive, more obvious. What would I do if Devlin ever caught me? Devlin The first time I saw her she was too young. I had to wait. I hated it, but I'd promised her mother I would wait for her to grow up. The sweet little waitress from Mae's diner was going to be mine. She just didn't know it yet. Contains mature themes.